Short-term effect of beinaglutide combined with metformin versus metformin alone on weight loss and metabolic profiles in obese patients with polycystic ovary syndrome: a pilot randomized trial - Wen, Qing; Fang, Song; Liang, Yanjing; Tian, Yuting; Chen, Yiding; Yuan, Jun; Chen, Qiu (Frontiers in Endocrinology, 2023)
Abstract Objective: To observe the effect of beinaglutide combined with metformin versus metformin alone on weight loss and metabolic profiles in obese patients with polycystic ovary syndrome(PCOS). Methods: A total of 64 overweight/obese women with PCOS diagnosed via the Rotterdam criteria were randomly assigned to metformin(MET) 850 mg twice a day(BID) or combined MET 850 mg BID with beinaglutide (COMB) starting at 0.1mg three times a day(TID)and increasing to 0.2mg TID two weeks later. The main endpoints were changes in anthropometric measurements of obesity. Glucose and lipid metabolic, gonadal profiles, and antral follicle count changes as secondary outcomes were also observed. Results: 60(93.75%) patients completed the study. In terms of lowering weight, body mass index (BMI),waist circumference(WC) and waist to height ratio(WHtR), COMB treatment outperformed MET monotherapy. Subjects in the COMB arm lost weight 4.543.16kg compared with a 2.473.59kg loss in the MET arm. In the COMB group, BMI,WC and WHtR were reduced significantly compared with that in the MET group, respectively. COMB therapy is also more favorable in the reduction of fasting insulin(FINS), total testosterone(TT), and homeostasis model assessment–insulin resistance(HOMA-IR) when compared to MET therapy. Antral follicle count and ovarian volume were non-significantly changed in both groups.The most frequent side effects in both groups were mild and moderate digestive symptoms. Itching and induration at the injection site were reported with COMB treatment. Conclusions: Short-term combined treatment with beinaglutide and metformin appears superior to metformin monotherapy in lowering body weight, BMI, WC ,WHtR and improving insulin sensitivity and androgen excess in women with PCOS and obesity, with tolerable adverse events.